The spoke wheel color Doppler blood flow signal is a specific sign of papillary thyroid carcinoma - Xue, Nianyu; Li, Ping; Deng, Huadong; Yi, Jing; Xie, Yu; Zhang, Shengmin (Frontiers in Endocrinology, 2022)
Background Papillary thyroid carcinoma (PTC) is the most common type of thyroid cancer. Grayscale ultrasound (US) is the main method used to diagnose benign and malignant thyroid nodules, While color doppler blood flow imaging(CDFI) is not widely recognized when diagnosing thyroid cancer. Methods This study used a retrospective analysis. The study included 36 spoked wheel blood flow nodules detected by CDFI in 37,372 patients in five hospitals from January 2020 to June 2021. All thyroid nodules were examined histologically after ultrasound-guided fine needle biopsy or following surgical resection. The value of color doppler in diagnosing papillary thyroid carcinoma was evaluated based on pathological results. Results Among 36 thyroid nodules, only 6 were highly suspected of being malignant on grayscale ultrasound (classified as 5, according to ACR TI-RADS). However, these 36 thyroid nodules showed spoke wheel blood flow signal distribution on CDFI. If the spoke wheel blood flow signal is used to diagnose papillary thyroid cancer, then the diagnostic accuracy of this group of papillary thyroid cancers can reach 100%, which is significantly higher than the accuracy of grayscale ultrasound diagnosis, and the difference is statistically significant (p<0.05). Conclusions The results of this study found that spoke wheel blood flow sign on CDFI can be used to diagnose PTC. PTC with spoke wheel blood flow have benign characteristics on gray-scale ultrasound, which is easy to be misdiagnosed.